Central giant cell granuloma of the maxilla: a case re-port - Alchalabi, Najwa; Salih, Hayder; Merza, Ahmed (International Journal of Dental Research, 2017)
Introduction: Central giant-cell is a benign lesion that predominantly involves the bone of the mandible and maxilla with a wide variation of its behavior. Surgery usually is the first choice in treatment of central giant cell granuloma.Case Report: In this case report we present a 29 years-old female with well define swelling on left maxilla. Diagnosis through incisional biopsy showed a central giant cell granuloma. Surgery with curettage was our treatment option with a follow up( 2 years ), No recurrence was reported.Discussion: Information on the maxillary central giant cell granuloma in published studies is insufficient. So here we present our case as unusual case presentation. Differential diagnosis of this case included osteosarcoma (parosteal type) since the tumor clinical presentation in periosteous tissue adjacent to the bone cortex and showed rapid growth. We chose the conventional surgical treatment by simple surgical curettage by mid-face degloving approach to avoid any facial scaring.